FACTORS ASSOCIATED WITH LOW BIRTH WEIGHT AMONG NEWBORNS IN ETHIOPIA - Jamie, Arif Hussen; Ahmed, Abduseme Mohammed (Public Health of Indonesia, 2020)
Background: Worldwide more than 20 million low birth weights occur annually with the incidence of 15 to 20%, majority of this occur in low- and middle-income countries and 95.6% occur in developing nations. Its regional estimate was 28% in South Asia, 13% in sub-Saharan Africa and 13% in least developed countryObjective:  To assess factors associated with low birth weight among newborns in Jugal Hospital, Harari Regional State, Ethiopia.Methods: A cross-sectional study was conducted among newborns in Jugal hospital, Ethiopia from June 01 to July 10, 2019. Systematic random sampling technique was used to select the study subjects. Multivariate logistic regression analysis was used to identify factors associated with low birth weight among newbornsResults: The magnitude of low birth weight was 19.53%. Women who had previous history of low birth weight had 5.21 times higher odds ratio of delivered low birth weight baby than their counterparts [AOR = 5.21, 95% CI: (1.5-14.2)], and pregnant women who delivered before 37 weeks of gestational age had 4.8 times higher odds ratio of delivered low birth weight neonates than those delivered at term [AOR = 4.8, 95% CI: (1.3-10.4)]Conclusion: The prevalence of low birth weight in Harar, Jugal Hospital was 19.53%. Low birth weight in the previous pregnancy and gestational age <37 weeks, and showed significant association with birth weight neonates. Governmental and non-governmental organizations working on maternal and child health should focus on identified factors in order to tackle the problem of birth weight.